Linear /nonlinear optical susceptibility spectroscopic constants of polyaniline@graphene oxide nanocomposite thin films - Jilani, Asim (Elsevier Ltd., 2019)
Graphene based conducting polymer composites are emerging contenders for newer optoelectronics devices like solar cells and linear / nonlinear optical devices. Beside these advanced applications, characterization approaches to analyze their liner/nonlinear optical constants, surface chemical state and structural analysis in thin film states are much needed. Herein, we reported a facile approach for the fabrication of graphene oxide (GO) and polyaniline (PANI) nano composites (PANI/GO) thin films using spin coating. Thereafter, the liner/nonlinear optical constants including first and third order nonlinear optical susceptibility were calculated using UV–vis (UV–vis) near infra-red absorption spectroscopic technique which will be an alternative to Z-scan approach and is poorly explored till now for such composites. Moreover, the increase or decrease in elemental bonding or interactions between C–C, C–O, C–O–C, C–N and percentage occurrence of C–OH, O–C[dbnd]O, –NH 2 , –N + H=, and –N + H 2 – functionalities in PANI/GO composites were concisely explored using X-ray photoelectron spectroscopy (XPS). Addition to proving the amorphous nature of PANI/GO composites in their X-ray diffraction studies, an increase in intensity of GO peak was explored due to an increase in elemental interactions among the GO and PANI. The reduction in band gap (3.27 to 2.66 eV) and diameter of Sp 2 carbon (19.62 to 15.96 nm) of PANI/GO thin films was observed with an increase in the GO concentration. The first order nonlinear optical susceptibility (X (1) ) is influenced by π-π* and n- π* interaction. The third order nonlinear optical susceptibility (X (3) ) was found in the range of 10 −10 to 10 -7 esu which can be further, optimized by changing the ratio of GO and PANI.